Resonance signatures in the body-frame valence photoionization of CF4. Issue 32 (3rd August 2018) - Larsen, K. A.; Trevisan, C. S.; Lucchese, R. R.; Heck, S.; Iskandar, W.; Champenois, E.; Gatton, A.; Moshammer, R.; Strom, R.; Severt, T.; Jochim, B.; Reedy, D.; et al.
Abstract : Photoionization of the 4t2 orbital of CF4 shows overlapping resonances close to threshold, leading to a striking inversion of the photoelectron angular distribution when viewed in the body-frame. Abstract : We present a combined experimental and theoretical investigation of the electron dynamics and body-frame angular dependence of valence photo-single ionization of CF4 and subsequent dissociation into CF3 + and F. Ionization from a valence t2 orbital shows overlapping shape resonances close to threshold that couple to the same total symmetry, leading to striking changes in the photoelectron angular distributions when viewed in the body-frame.